Grade 8 Learners’ Impediments When Learning Geometry: A Case Of One High School, Eastern Cape South Africa - Chiphambo, Shakespear Maliketi (IndoMath: Indonesia Mathematics Education, 2024)
The study aimed to identify and understand the specific challenges that Grade 8 learners face in learning geometry within the context of one high school in the Eastern Cape region of South Africa. The study explores Grade 8 learners’ impediments when learning geometry. The study uses van Hiele’s geometric thinking theory which provides the framework for how learners learn geometry. The study employed a qualitative approach guided by the case study design and subjected textual qualitative data to thematic content analysis. Nine Grade 8 learners were purposely selected from the cohort of 56 learners using diagnostic test results. The study reveals impediments that inhibit learners from performing well in geometry, such as lack of mathematical language proficiency, failure to make meaning of the mathematical concepts and terminology, lack of English language proficiency, poor teaching methods, and learners’ negligence of mathematical rules. The study recommends mathematics teachers implement language support strategies for learners, develop learners’ conceptual understanding of geometry, emphasize symbolic representation when teaching, support learners’ English language development, engage learners with geometry rules, make use of differentiated instruction, promote a growth mindset, and ask the Department of Education to provide professional development for educators.